2003
DOI: 10.1093/intqhc/mzg076
|View full text |Cite
|
Sign up to set email alerts
|

User satisfaction with a real-time automated feedback system for general practitioners: a quantitative and qualitative study

Abstract: Apart from securing agreement on guideline content, a prerequisite for using GRIF in daily practice on a large scale is that more attention is paid to promotion of the guidelines and their adoption, and stimulation of a positive attitude towards the practice guidelines among the users.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
5
0

Year Published

2004
2004
2017
2017

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 12 publications
(5 citation statements)
references
References 27 publications
0
5
0
Order By: Relevance
“…Likewise, it has been demonstrated that health information technology has significant potential for improving the processes of care while being cost‐effective [11]. Feedback has enhanced adherence to guidelines on chronic care [12–14], but evidence on the effect of electronically delivered feedback for the quality of Type 2 diabetes care is less convincing [15]. Thus, the aim of this study was to evaluate the effect of an electronic feedback system to general practitioners on the quality of care for people with Type 2 diabetes.…”
Section: Introductionmentioning
confidence: 99%
“…Likewise, it has been demonstrated that health information technology has significant potential for improving the processes of care while being cost‐effective [11]. Feedback has enhanced adherence to guidelines on chronic care [12–14], but evidence on the effect of electronically delivered feedback for the quality of Type 2 diabetes care is less convincing [15]. Thus, the aim of this study was to evaluate the effect of an electronic feedback system to general practitioners on the quality of care for people with Type 2 diabetes.…”
Section: Introductionmentioning
confidence: 99%
“…[3][4][5] Ahearn and Kerr acknowledged that there is little information available about the attitudes of Australian general practitioners (GPs) to decision support software. 6 In their qualitative study of 22 GPs, they identified that doctors need to remain sensitive to their patients' needs and expectations.…”
Section: Introductionmentioning
confidence: 99%
“…Computerized provider order entry is an attractive vehicle for delivery of evidence-based clinical guideline information at the point of care. 26,27 Various methods of presentation of guideline information have been reported, including context-specific links to intranet or Internet information sources, 28 immediate feedback during the ordering process, 29 printed reminders during routine outpatient visits, 30 alerts and reminders triggered by orders, 16 and the use of order-sets that are consistent with guidelines. 31 Full realization of the potential for integrated guidance with CPOE remains limited by the difficulty of representing guideline knowledge in computerized order entry systems, 32,33 lack of structured, patient-specific information available for computer analysis at the point of care, and provider perceptions that the computer generated suggestions are strictly related to attempts at cost-reduction rather than quality of care.…”
mentioning
confidence: 99%